The effect of protein intake on athletic performance: a systematic review and meta-analysis - Zhao, S.; Zhang, H.; Xu, Y.; Li, J.; Du, S.; Ning, Z. (Frontiers in Nutrition, 2024)
Background: The impact of a protein-rich diet and protein supplements on athletic performance remains a topic of debate. Does protein intake offer benefits for athletes? If so, which specific aspects of athletic performance are most influenced by protein?